Activity profile of training and matches in Brazilian Olympic female soccer team - Passos Ramos, G.; Datson, N.; Mahseredjian, F.; Ribeiro Lopes, T.; Celso Coimbra, C.; Sales Prado, L.; Nakamura, F. Y.; Macedo Penna, E. (Science and Medicine in Football, 2019)
Objective: This study compared the activity profile of different types of soccer-specific training activity with the demands of competitive international female match-play. Methods: Twenty-one female players from the Brazilian National Soccer Team were monitored in twenty-two on-field training sessions during the 30-day preparatory training camp prior to the 2016 Olympic Games. Activities were categorized into warmup (WU), small sided games (SSG), technical and tactical training (TTT) and friendly matches (FM). The activity profile in each type of drill was then compared to the ones of the 6 matches performed during the Rio 2016 Olympic Games. Results: It was found that distance traveled at different speeds were higher during matches compared to WU, SSG, and TTT, but not compared to FM. Frequency of accelerations was similar between matches and TTT, SSG and FM. Repeated acceleration and sprints were higher during Matches compared to WU, TTT, SSG but FM presented similar results. Conclusion: It was concluded that although there were different acceleration and deceleration demands amongst WU, SSG and TTT compared to match-play, FM was the only training activity which consistently replicated or exceeded Olympic matches` physical demands.